Emerging drugs for the treatment of diabetic retinopathy. (2nd July 2020) - Striglia, Elio; Caccioppo, Andrea; Castellino, Niccolò; Reibaldi, Michele; Porta, Massimo
ABSTRACT: Introduction: Diabetic retinopathy (DR) is one of the main pathological features of the diabetes mellitus spectrum. It is estimated that in 2020 about 4 million people worldwide suffered from blindness or visual impairment caused by DR. Many patients cannot access treatment, mostly because of high costs, while others discontinue it prematurely due to the high number of intravitreal administrations required, or the occurrence of ocular complications, or discomfort in quality of life. Areas covered: The aims of this paper are to summarize the current understanding of the pathogenesis and treatment of diabetic retinopathy, focus on the most promising new approaches to treatment that are being evaluated in clinical trials, and outline the potential financial impact of new drugs in future markets. Expert opinion: Slow-release systems with steroids, anti-VEGF or sunitinib are promising. Oral imatinib would avoid the ocular complications of intravitreal drugs. Brolucizumab and abicipar pegol may be superior to aflibercept and ranibizumab with the advantage of less frequent administrations. Faricimab, active on Tie-2 receptors, is being evaluated in two phase 3 clinical trials. Further knowledge of the efficacy and safety of these drugs is necessary before their final approval for the treatment of diabetic retinopathy.